A Review of Antecedents of International Strategic Alliance Performance: Synthesized Evidence and New Directions for Core Constructs. (12th April 2012) - Christoffersen, Jeppe
<x xml:space="preserve">Abstract</x> This paper provides a systematic review of 165 empirical studies on the antecedents of performance in international strategic alliances. It provides the most detailed display of definitions, rationales, measures and findings currently available. Hence, this state‐of‐the art literature review creates an accessible pool of knowledge that is highly relevant for future research on international strategic alliances. Further, it draws on this knowledge pool to build a model which highlights the quite different rationales advanced by researchers to explain associations between the antecedents and performance. The model makes the different rationales explicit and will aid researchers in identifying tests that can be performed to examine the links between antecedents and performance as well as the mechanisms through which such associations operate. Finally, the synthesized evidence is used to suggest that researchers should give increased attention to achieving congruence between measures of antecedents and performance.